Turbidity and color removal from irrigation water, with coagulants and activated carbon, controlled by an Arduino system - Meregildo Collave, Christian Xavier (2023)
The Moche River water is contaminated due to informal mining and other anthropogenic activities. The pollutants are primarily organic matter and heavy metals, which contribute to the water’s elevated color and turbidity levels. This contaminated water is used for irrigating surrounding areas, leading to the production of contaminated crops. Monitoring color and turbidity requires expensive instruments. In this study, a water sample was collected from the district of Poroto, located in the province of Trujillo, La Libertad region. Approximately 200 L were sampled, with a pH of 5.2 and a turbidity of 12.04 NTU. The research employs a combined treatment process involving coagulants, specifically ferric sulfate and polyaluminum chloride, followed by filtration through activated carbon. Additionally, a low-cost monitoring system using an Arduino-based turbidimeter and colorimeter is proposed to measure water quality before and after treatment. The system incorporates a TS-300B turbidity sensor and a custom-built Arduino colorimeter utilizing the BPW34 sensor. Experimental results show a maximum color removal efficiency of 95.71% and a turbidity reduction of 70.43% under optimal conditions. The activated carbon used had the following properties: an iodine number of 902.85 mg/g, 10.73 mmol of acidic groups, and a point of zero charge (PZC) of 9.3. The turbidimeter and colorimeter cost $40.46 and $58.15, respectively. Validation parameters for the instruments were as follows: Pearson correlation coefficient of 99.98%, MAE of 2.46, RMSE of 3.80, and MAPE of 2.18% for the turbidimeter, and Pearson correlation coefficient of 99.73%, MAE of 0.07, RMSE of 0.08, and MAPE of 9.44 % for the colorimeter. This innovative solution demonstrates the feasibility of using low-cost technology for effective water treatment, contributing to sustainable agricultural practices by improving irrigation water quality and promoting better crop health and environmental protection.